Electrospun Composite Bead-on-String Nanofibers Containing CaO2Nanoparticles and MnO2Nanosheets as Oxygen-Release Systems for Biomedical Applications - Dos Santos, Danilo M.; Dias, Luana M. [UNESP]; Surur, Amanda K. [UNESP]; De Moraes, Daniel A.; Pavarina, Ana C. [UNESP]; Fontana, Carla R. [UNESP]; Correa, Daniel S. (American Chemical Society (ACS), 2022)
Oxygen-generating biomaterials have the potential to improve tissue engineering and regenerative therapeutic strategies. However, the development of such materials capable of controlling the local partial pressure of oxygen (pO2) in the long term is still a major challenge. Here we report nanostructured composite membranes comprising electrospun fibers exhibiting a bead-on-string structure as a controlled oxygen-release system for periodontitis treatment. For this, calcium peroxide nanoparticles (CaO2NPs) and manganese dioxide nanosheets (MnO2NSs) were incorporated into the structure of hydrophobic electrospun poly (lactic acid) (PLA)-based nanofibers. We use CaO2NPs as hydrogen peroxide (H2O2)-generating precursors when exposed to water, while MnO2NSs were applied as a nanozyme to catalyze the decomposition of H2O2to the final oxygen product. Our results revealed that the beads on the fibrous structure acted as reservoirs of CaO2NPs and MnO2NSs. Moreover, the composite membranes provided sustained oxygen release over 7 days, where levels were modulated by the CaO2NP content. Such constructs exhibited suitable physicochemical properties and antimicrobial activities against some bacteria (e.g., Porphyromonas gingivalis and Treponema denticola) typically associated with aggressive and chronic periodontitis. In vitro studies also revealed that the membranes were not cytotoxic toward human oral keratinocyte (Nok-si) cells as well as enhanced the cell viability when high content of CaO2NP and MnO2NS were incorporated into the fiber's structure. Taken together, our results demonstrate that the nanostructured composite membranes show potential to be employed as oxygen-release platforms for periodontal tissue regeneration.
Keywords: bead-on-string fibers; composite membranes; electrospinning; oxygen generation; periodontal regeneration, hybrid materials